Factors influencing the distribution of Chl-a along coastal waters of East Peninsular Malaysia - F. Shaari,; M.A. Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Determination of chlorophyll-a (Chl-a) distribution in the coastal waters is important to understand the coastal environmental conditions. This study was conducted to understand the spatial and temporal distribution of Chl-a along coastal waters of east Peninsular Malaysia and factors influencing its variability using Chl-a data derived from Aqua MODIS satellite (1 km spatial resolution) from January 2006 to December 2012. Chl-a variability was described using empirical orthogonal function (EOF) analysis. In-situ data (temperature, salinity, density and nitrate) and rainfall data from the Department of Meteorology were analyzed using spatial interpolation to determine factors influencing the distribution of Chl-a. The seasonal progressions of Chl-a showed high value during northeast monsoon along the coast. This variability was described by four modes of the EOF analysis. The first mode (72.08% of total variance) indicated seasonal cycle with high variability along the coast. Second mode (17.03% of variance) explained the northeast monsoon with high variability from river mouth to the south. Third mode (2.39% of variance) indicated variability during southwest monsoon along the coast and much higher to the south. Mode 4 (1.93% of variance) explained the inter-monsoon period observed along the northern and southern coastline. Concentration and distribution of Chl-a were related to availability of nutrient influenced by rainfall. The thermohaline front was also observed to play an important role in accumulation of phytoplankton biomass during northeast and southwest monsoon.